Предмет: Алгебра,
автор: tden121
Выполните преобразование по формуле:
a) (y+3)^2
б) (4x+7)^2
в) (5-a)^2
г) (2x-3)^3
д) (2x-3y)(4x^2+6xy+9y^2)
е) 5(x-4)+(x-4)(x+4)
Ответы
Автор ответа:
2
1)у²+6у+9
2)16х²+56х+49
3)25-10а+а²
4)8х³-36х²+54х
5)8х³-27у³
6)5(x-4)+(x-4)(x+4)=(х-4)(5+х+4)=(х-4)(х+9)
2)16х²+56х+49
3)25-10а+а²
4)8х³-36х²+54х
5)8х³-27у³
6)5(x-4)+(x-4)(x+4)=(х-4)(5+х+4)=(х-4)(х+9)
tden121:
Спасибо!
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: Литература,
автор: rottenmilkk
Предмет: Физика,
автор: gudaa778
Предмет: Обществознание,
автор: YanaVip